P-P17 Casting a Wider NET: Defining PEI in patients with Neuroendocrine Tumours using the 13C-MTG breath test. (16th December 2021) - Hall, Lewis; Powell-Brett, Sarah; Bradley, Elizabeth; Thompson, Oscar; Smith, Stacey; Vickrage, Suzanne; Kemp-Blake, Joanne; Shah, Tahir; Roberts, Keith
Abstract: Background: Somatostatin-analogues (SSAs) are the first-line treatment of unresectable, symptomatic neuroendocrine tumours (NETs). However, SSAs inhibit pancreatic secretions which could lead to pancreatic exocrine insufficiency (PEI). There is, however, very limited data regarding the physiologic link between SSAs and PEI. PEI negatively impacts patient quality of life (QoL), nutritional status, and clinical outcomes. This is a prospective, observational, cohort study to establish the impact of SSAs on pancreatic exocrine function in patients with NETs, using the 13 C-Mixed-Triglyceride ( 13 C-MTG) breath test. Methods: Adult patients commencing SSA therapy for NETs, were recruited from December 2020. Patients were excluded if they had a diagnosis of other pancreatic disease, history of upper-gastrointestinal surgery that may alter pancreatic function, or already on SSA therapy. The impact of SSAs on exocrine function was assessed using the 13 C-MTG breath test. A quotient of 13 CO2 / 12 CO2 was measured by mass spectrometry and the cumulative percent dose recovered at 6 hours (cPDR) is reported. Secondary endpoints investigated were changes in patient weight and Vitamin D levels. Results: Exocrine function reduced in all patients (n = 7) following SSA therapy (median reduction from baseline: -22.2%, range: -5.6- -42.1%; p = 0.018) (Figure 1 ) . Vitamin D levels decreased in all but one patient (median decrease from baseline: -11.7%, range: -29.3-10%; p = 0.126). Change in patient weight did not show any significant change (median decrease from baseline: -0.69%, range: -4.26 – 3.6%, p = 0.933). Conclusions: SSA therapy appears to have a consistent impact on exocrine function from early in the treatment course. This suggests that there is a widespread underestimation of PEI in this setting. Whether such decrease in exocrine function leads to weight loss remains to be seen. Further studies are required to confirm this work, determine the clinical relevance of this observation, and optimise medical therapy of PEI in this cohort. The 13 C-MTG breath test is a feasible and acceptable measure of pancreatic exocrine function in patients treated with SSA therapy for NETs.